Diurnal glycemic fluctuation is associated with severity of coronary artery disease in prediabetic patients: Possible role of nitrotyrosine and glyceraldehyde-derived advanced glycation end products. Issue 4 (April 2017) - Watanabe, Makoto; Kawai, Yasuyuki; Kitayama, Michihiko; Akao, Hironubu; Motoyama, Atsushi; Wakasa, Minoru; Saito, Ryuhei; Aoki, Hirofumi; Fujibayashi, Kousuke; Tsuchiya, Taketsugu; Nakanishi, Hiroaki; Saito, Kazuyuki; et al.
Abstract: Background: Glucose fluctuation (GF) is a risk factor for coronary artery disease (CAD). However, it remains unknown whether specific indices of GF are risk factors for CAD. Therefore, we evaluated the relationship between GF, as determined by a continuous glucose monitoring system (CGMS) or the glucose level at 2 h after a 75-g oral glucose tolerance test (75 g OGTT 120), and the severity of CAD in prediabetic patients. We also evaluated whether nitrotyrosine (NT) and glyceraldehyde-derived advanced glycation end-products (Glycer-AGE) were induced by GF. Methods: Twenty-eight prediabetic patients underwent coronary angiography (CAG), and the Gensini score and the SYNTAX score were evaluated as the severity of CAD, while the mean amplitude of glycemic excursions (MAGE) by CGMS and 75 g OGTT 120 were evaluated. Serum NT and Glycer-AGE were measured. Results: The MAGE was closely associated with the Gensini score ( r = 0.742, p < 0.001) and the SYNTAX score ( r = 0.776, p < 0.001), respectively. The 75 g OGTT 120 was not associated with the Gensini score ( r = 0.36, p = 0.06), but it was significantly associated with the SYNTAX score ( r = 0.413, p = 0.036). Multiple linear regression analysis showed that the MAGE was the only independent determinant for the severity of CAD. The levels of NT and Glycer-AGE were significantly higher in the high MAGE group than in the low MAGE group. Conclusions: Diurnal GF is associated with the severity of CAD, even in prediabetic patients. GF, NT, and Glycer-AGE may play a pathological role in the progression of CAD.